Fish Species Composition and Diversity of Small Riverine Ecosystems in the Lake Victoria Basin, Kenya - Mwangi, Benson M.; Ombogo, Mornica A.; Amadi, Jacinta; Baker, Ntambi; Mugalu, Daniel (My University, 2012)
Riverine ecosystems in the Lake Victoria Basin (LVB) significantly contribute to the lake’s water budget and aquatic biodiversity. Despite their significance to the lakes fisheries, only limited biodiversity studies have been carried out, particularly in the smaller riverine ecosystems. This study investigated the fish species composition, diversity and distribution in two small riverine ecosystems (Rivers Awach Seme and Kisian) draining the Kenyan Lake Victoria Basin. Sampling was carried out monthly from August 2009 to June 2010, at three sampling sites of 100-m stretch along each river, representing the upper, middle and lower reaches. Fish were caught using an electro-fisher, identified with the help of relevant taxonomic guides and staff from the Kenya Marine and Fisheries Research Institute, measured for total lengths and weighed to the nearest 0.1 cm and 0.1 gm, respectively. The results showed that the two rivers had a diverse fish community consisting of 11 species, namely, Barbus altianalis Boulenger, Labeo victorianus Boulenger, Barbus cercops Whitehead, Clarias gariepinus Burchell, Barbus nyanzae Whitehead, Barbus kerstenii Peters, Barbus jacksonii Günther, Barbus appleurograma, Oreochromis leucostictus Trewavas, Gambusia affinis Baird & Girard, and Bagrus docmak Forsskål, out of which 9 were present in River Kisian and 7 in River Awach. The fish community at River Kisian was dominated by C. gariepinus, constituting over 42.5% while at River Awach, B. altianalis and B. nyanzae dominated with over 46.3% and 30.7% of the total catch, respectively. Fish abundance and evenness were much higher in River Awach suggesting that this river would provide better fisheries if managed appropriately. Generally, the results show that the two rivers may be an important source of fish for both the lakes ecosystem as well as local fisheries if appropriate management interventions are instituted
Keywords: Lake Victoria Basin; riverine fisheries; Clarias; Kisian; Awach-Seme